2003
DOI: 10.1080/00087114.2003.10589351
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic characterization of hybrids offspring betweenColossoma macropomum(Cuvier, 1818) andPiaractus brachypomus(Cuvier, 1817) from Caicara del Orinoco, Venezuela

Abstract: Conventional karyotype and nucleolar organizer regions (NORs) of C. macropomum x P. brachypomus hybrids and parental species are reported. A modal diploid number of 54 chromosomes and a fundamental number (NF) of 108 were found for C. macropomum, P. brachypomus and their hybrids. P. brachypomus shows a pair of silver stained chromosomes, while cells with three and four Ag-NOR bearing chromosomes were observed in C. macropomum. The hybrids consistently presented cells with a single metacentric Ag-NOR bearing ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 9 publications
6
21
0
Order By: Relevance
“…A number of researchers have found that most inter-generic hybrids can fertilize and hatch (Nirchio et al, 2003;Lou and Li, 2006;Hashimoto et al, 2012). This is consistent with our results that demonstrate that fertilization and hatching can be achieved using four inter-generic reciprocal crosses of transparent crucian carp with ornamental carp and red purse carp.…”
Section: Discussionsupporting
confidence: 81%
“…A number of researchers have found that most inter-generic hybrids can fertilize and hatch (Nirchio et al, 2003;Lou and Li, 2006;Hashimoto et al, 2012). This is consistent with our results that demonstrate that fertilization and hatching can be achieved using four inter-generic reciprocal crosses of transparent crucian carp with ornamental carp and red purse carp.…”
Section: Discussionsupporting
confidence: 81%
“…Lepisosteus osseus (Ráb et al, 1999), with only one Ag-NOR-bearing chromosome pair, the FISH technique using 18S or 28S sequences usually stains the same chromosome pair. Nevertheless, the presence of a number of major ribosomal cistrons identified by the FISH technique using 18S or 28S sequences higher than that observed with the Ag-NOR technique are more common, having been reported in Salmo truta (Pendás et al, 1993), Astyanax scabripinnis (Ferro et al, 2001), Hyphessobrycon anisitsi (Centofante et al, 2003), Prochilodus lineatus (Jesus and Moreira-Filho, 2003), Colossoma macropomum, Piaractus brachypomus and its interspecific hybrids (Nirchio et al, 2003), and Lebias fasciata (Tigano et al, 2004). These differences have been attributed to the presence of NORs that are usually unexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…Ag-NORs in Serrasalmidae have been analyzed since the 1980s and have invariably been visualized as multiple sites usually located in the terminal region on the short arms of subtelo-acrocentric chromosomes, although some species bear terminal Ag-NORs on the long arms (Galetti Jr. et al, 1985;Almeida-Toledo et al, 1987;Cestari & Galetti Jr. 1992a, b;Martins-Santos et al, 1994;Nakayama et al, 2001Nakayama et al, , 20022008;Centofante et al, 2002a;Nirchio et al, 2003;Gaviria et al, 2005). However, the numerical variation in these regions (in both inter and intra-specific terms) is much more notable than the positional differences, ranging from four sites in C. macropomum to 12 sites in S. rhombeus (Table 1).…”
Section: Discussionmentioning
confidence: 99%